Fluorescent in situ hybridization (FISH)-a quick screening tool for female children with palpable gonads for excluding androgen insensitivity syndrome - Mrinal Arora; Noor Ullah Zargar; Anurag Krishna (SpringerOpen, 2023)
Abstract Background The incidence of inguinal hernia in the pediatric population is 0.8-4.4% with a male to female ratio of 5:1.The reported incidence of sliding hernia containing an ovary in female infants and children is 15-20%.The complete androgen insensitivity syndrome occurs in 1-2% of girls with an inguinal hernia. Thus, the incidence of CAIS in females with hernias and palpable gonads is 4/1,000,000. Results This is a retrospective analysis of 694 children that had undergone inguinal hernia repair in last 11 years. Out of these, 123 were females, 36 cases had palpable gonads at the time of presentation. FISH analysis was done in 29 cases (80%). None of the cases showed the presence of the Y chromosome. An abnormal chromosomal pattern was seen in one case on complete karyotyping. Conclusion The reported incidence of CAIS in girls with inguinal hernia is low, thus subjecting every girl child with inguinal hernia to undergo karyotyping is distressing for the parents. FISH analysis is an effective screening modality to rule out CAIS in girls with an inguinal hernia. Thus, it is recommended to screen only high-risk cases with palpable gonads at presentation.